Peningkatan Kemampuan Komunikasi Orang Tua-Anak pada Keluarga Penerima Manfaat Program Keluarga Harapan Kelurahan Banjarsari Kota Metro - Ita Prihantika; Moch. Johan Pratama; Hani Damayanti Aprilia; Nurul Utami (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2023)
The Covid-19 pandemic not only has an impact on physical health, but also psychological health. The Covid-19 pandemic, one of which has an impact on various violations of children's rights committed by parents. Banjarsari Subdistrict revealed that children's activities in online learning have not been optimal, there is misparenting (verbal violence) so that the use of free time in activities that are not useful. This PKM activity is specifically aimed at improving the main skills of mothers in communicating with children to maintain maternal mental health in parenting patterns through responsive and positive parenting approaches. The target of this activity is PKH recipient families who will become agents of change in society. The results of this devotion: (1) cognitive changes occurred, namely an average increase of 0.56 (normal); (2) the willingness of service participants to form a mental health care community for PKH Beneficiary Family groups in Banjarsari Village.